Effectiveness and Spatial Distribution of Wastewater Land Application Technical Approval in East Java - Hakasmanti, Erika; Semedi, Bambang; Hardjoko, Arief Tri; Koentjoro, Maharani Pertiwi; Supriyadi, Supriyadi (Universitas Diponegoro, 2026)
The management of industrial wastewater presents a considerable challenge to governments globally, mainly because of the difficulties faced in ensuring that regulatory frameworks are properly instituted. This study evaluated the success of the technical approval for using wastewater